2019
DOI: 10.1186/s13229-019-0270-8
|View full text |Cite
|
Sign up to set email alerts
|

Retinal alterations in a pre-clinical model of an autism spectrum disorder

Abstract: Background: Autism spectrum disorders (ASD) affect around 1.5% of people worldwide. Symptoms start around age 2, when children fail to maintain eye contact and to develop speech and other forms of communication. Disturbances in glutamatergic and GABAergic signaling that lead to synaptic changes and alter the balance between excitation and inhibition in the developing brain are consistently found in ASD. One of the hallmarks of these disorders is hypersensitivity to sensory stimuli; however, little is known abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 63 publications
(75 reference statements)
2
20
0
Order By: Relevance
“…In another study of Fmr1 knockout mice, both a-wave and b-wave amplitudes in scotopic ERG were decreased 18 . Interestingly, a recent article reported that in the valproic acid induced mouse model of ASD, a-wave amplitudes were smaller yet b-wave amplitudes were normal in scotopic ERG 20 , similar to what we observed here. Thus, it appears that a decrease in a-wave amplitude is shared by idiopathic and syndromic mouse models of ASD.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In another study of Fmr1 knockout mice, both a-wave and b-wave amplitudes in scotopic ERG were decreased 18 . Interestingly, a recent article reported that in the valproic acid induced mouse model of ASD, a-wave amplitudes were smaller yet b-wave amplitudes were normal in scotopic ERG 20 , similar to what we observed here. Thus, it appears that a decrease in a-wave amplitude is shared by idiopathic and syndromic mouse models of ASD.…”
Section: Discussionsupporting
confidence: 91%
“…Similar cortical recordings and behavioral tests could be applied to the BTBR mice as well, to further our understanding of the visual phenotype reported here. In addition, the anatomical and biochemical characterization of the retina and visual cortex, used in previous studies, provides a useful guide [15][16][17][18][19][20] , which could be followed in subsequent studies to investigate possible structural or biochemical rearrangements underlying the altered visual function in BTBR mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst abnormalities in glutamate receptor expression may explain the findings in ASD, there are possibilities that glutamate transporters and regulators of neuronal development, such as fragile-X mental retardation protein (FMRP) or mGLUR5, which regulates FMRP expression, may also be involved. Recent studies in a rodent model of ASD (Guimaraes-Souza et al 2019) found approximately 1.5 x more expression of FMRP and mGLUR5 proteins in the outer and inner plexiform layers which may contribute to an altered signaling between neurons in the outer and inner retina.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Constable et al (2016) examined the LA-ERG bwave amplitude and found it was smaller at certain flash strengths. The novel LA-ERG observations of Constable et al (2016) are supported by evidence of altered ERGs from rodent models of neurodevelopmental disorders in ASD (Zhang et al 2019;Guimaraes-Souza et al 2019), Fragile X syndrome (Rossignol et al 2014) and ADHD (Dai et al 2017). Additional benefits of studying the LA-ERG are that the greater complexity of the cone pathways makes the LA-ERG an excellent tool for probing the detail of a retina's response to light McCulloch et al 2019), and, because it does not require 20 minutes adapting to darkness, the LA-ERG is a quicker and more acceptable assay than the DA-ERG.…”
mentioning
confidence: 84%